CALCULATION OF MARTENSITE HABIT PLANE FOR IN-TL ALLOY - KUZUCU, Y; DOGAN, A; CEYLAN, M (Council Scientific Industrial Research, 1991)
The method of Zhang J M [J Phys F (GB), 14 (1984) 769] used for obtaining the habit plane of martensite phase by using some polarized elastic waves propagating in an isotropic media was applied for an anistropic media. By using the elastic constants measured for the In-Tl alloy in the M(s) martensite starting temperature region, the martensite habit plane was calculated.